A NEW EARLY MIOCENE (AQUITANIAN) ELASMOBRANCHII ASSEMBLAGE FROM THE LA GUAJIRA PENINSULA, COLOMBIA (Ameghiniana, 2016)
Recent field expeditions have led to the discovery of a selachian assemblage from the earliest Miocene (Aquitanian) deposits of the Uitpa Formation in the La Guajira Peninsula, Colombia. This elasmobranch assemblage provides a unique glimpse into the Caribbean biodiversity at the onset of the Neogene. The assemblage consists of 13 taxa, of which some are reported from Miocene deposits for the very first time. There are also new records of taxa the in southern Caribbean region. The taxonomic composition of the selachian assemblage was used to conduct a paleoenvironmental and paleobathymetric analysis of the lower Uitpa Formation. The maximum likelihood estimation of paleobathymetry suggests that the lower part of the Uitpa Formation was probably accumulated at a water depth of 100 to 200 m. This indicates a rapid increase in relative sea level or basin deepening, providing new insights into the possible causes of marine biota changes in the Cocinetas Basin during the Oligocene/Miocene transition. Resumen. UN NUEVO ENSAMBLE DE ELASMOBRANCHII DEL MIOCENO TEMPRANO (AQUITANIANO) DE LA PENÍNSULA DE LA GUAJIRA, COLOMBIA. Recientes trabajos de campo han llevado al descubrimiento de un conjunto de seláceos procedente del Mioceno temprano (Aquitaniano) en los depósitos más antiguos de la Formación Uitpa en la Península de La Guajira, Colombia. Este conjunto de elasmobranquios provee una visión única de la paleobiodiversidad del Caribe a inicios del Período Neógeno. El conjunto aquí descrito se compone de 13 taxones, algunos de los cuales son reportados por vez primera para el Mioceno. Esta fauna también incluye nuevos registros para la región sur del Caribe. La composición taxonómica del nuevo ensamble permitió realizar un análisis paleoambiental y paleobatimétrico en la sección más inferior de la Formación Uitpa. La estimación de paleobatimetría usando maximum likelihood sugiere que la parte inferior de la Formación Uitpa fue probablemente depositada a profundidades entre los 100 y 200 m. Esto indica un rápido incremento en el nivel relativo del mar o en la profundización de la cuenca, proveyendo nueva información sobre las posibles causas que dieron origen a los cambios en la biota marina de la Cuenca de Cocinetas durante la transición del Oligoceno/Mioceno.